2016
DOI: 10.1177/1475725716642116
|View full text |Cite
|
Sign up to set email alerts
|

Psychology Degree Beliefs and Stereotypes: Differences in the Perceptions of Majors and Non-Majors

Abstract: Very little research examines the beliefs and stereotypes students have about the discipline and major of psychology. Previous research has found that psychology majors report hearing a variety of such beliefs and stereotypes more often from their fellow students than from their family members. In the current study, psychology majors/minors and non-majors/-minors (N ¼ 376) reported their frequency of hearing beliefs and stereotypes from friends/fellow students or family members and the extent that they agreed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Young people are challenged with popular images of psychology and psychologists that may lead to myths and misconceptions about the discipline and influence their motivations for studying. A number of studies on misconceptions about the field of psychology (e.g., Brinthaupt et al, 2016; Furnham & Hughes, 2014; Kowalski & Taylor, 2011; Lamal, 1979; Landau & Bavaria, 2003; McKeachie, 1960; Rosenthal et al, 2001; Vaughan, 1977; von Sydow, 2007) have revealed that both pre-university and university students have misconceptions and false beliefs concerning both the content of its study and professional paths the study of psychology affords.…”
Section: Motivation Toward Studying Psychologymentioning
confidence: 99%
“…Young people are challenged with popular images of psychology and psychologists that may lead to myths and misconceptions about the discipline and influence their motivations for studying. A number of studies on misconceptions about the field of psychology (e.g., Brinthaupt et al, 2016; Furnham & Hughes, 2014; Kowalski & Taylor, 2011; Lamal, 1979; Landau & Bavaria, 2003; McKeachie, 1960; Rosenthal et al, 2001; Vaughan, 1977; von Sydow, 2007) have revealed that both pre-university and university students have misconceptions and false beliefs concerning both the content of its study and professional paths the study of psychology affords.…”
Section: Motivation Toward Studying Psychologymentioning
confidence: 99%
“…Stepping out of the comfort zone and collaborating with corporations and companies can benefit the field in multiple ways. First it could reduce the belief that psychology undergraduate degrees are useless (Brinthaupt, Hurst, & Johnson, 2016) by establishing professional connections to learn how undergraduate education in psychology can be tailored and producing graduates who have applied skills that are desired. This collaboration could better link undergraduate training with meaningful job opportunities in the communities that are desired by both employers and graduates.…”
Section: Collaboration With Local and National Agenciesmentioning
confidence: 99%
“…Linderberg’s philosophy of teaching echoes the discussion of complexity of teaching in recognizing that there is an “unending list of characteristics of an excellent teacher.” But she focuses on key features which work for her students. Her goal is “to teach the students the scientific nature of psychology and hopefully show them how psychology is ubiquitous.” A focus on foundational issues of the science of the discipline and its application is notable, given the stereotypes held about the discipline and challenges in overcoming them (Amsel, Ashley, Baird, & Johnston, 2014; Brinthaupt, Hurst, & Johnson, 2016; Pettijohn et al, 2015). It also represents an important pedagogical and curricular movement away from the personal and more toward the scientific within the teaching of high school psychology (Keith, Hammer, Blair-Broeker, & Ernst, 2013)…”
Section: Mary Margaret Moffett Memorial Teaching Excellence Awardmentioning
confidence: 99%